Pengaruh Panjang Pipa Katalis Annulus Konsentris Pada HCS (Hydrocarbon Cracking System) Terhadap Torsi Motor Bakar 4-Langkah - Masruri Wardhana; Nasrul Ilminnafik; Sumarji Sumarji (STATOR: Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
HCS (Hydrocarbon Cracking System) is an innovation to improve torque and fuel. with copper catalyst pipe used as a tool to accelerate the process of fuel cracking in the combustion chamber. This study aims to obtain data comparison of the performance of 4-step fuel motor with variation of catalyst pipe length with standarts conditions as a comparison. In the research done by testing that is torque. From the results of research conducted torque value has increased with the use of catalyst pipe, the highest torque occurs in the condition of the catalyst pipe with a length of 200 mm with a torque of 9.32 Nm at RPM 3040. For catalysts with a length of 150 mm and 100 mm the value of torque obtained is 9.23 Nm and 9.16 Nm, while the standard torque condition is only 9.13 Nm. The cracking process in the catalyst pipe causes CH to split fuel into C and H atoms, in the presence of H atoms on fuel, the fuel mixture becomes more ideal and combustible in the combustion chamber. The length of the catalyst pipe will increase the amount of hydrocarbons and purity of hydrogen and carbon without the content of H2O. the ideal fuel composition will increase combustion and maximum torque value Keywords: HCS, Torque, Cracking System, Length of Catalyst